Preparation method of normal-pressure drying type polysaccharide aerogel without replacement of organic solvent
By using a mixed solution of nanocellulose, surfactant and carbonate powder under normal pressure to form wet foam, cure and dry in the acidic solution, the problems of high cost and environmental risks of the existing aerogel process are solved. A low-cost, green cellulose aerogel preparation is achieved, with lightweight porous properties.
Patent Information
- Application Number
- CN202411264221.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
AI Technical Summary
The existing aerogel preparation process requires supercritical conditions, harsh equipment and high costs, and the replacement process using organic solvents poses environmental and safety risks, making it difficult to achieve low-cost green biomass aerogel production.
A mixed solution of nanocellulose dispersion, surfactant and insoluble carbonate powder is used to form a wet foam precursor through high-speed stirring, which is cured in the acidic solution and dried under normal pressure, avoiding solvent replacement steps, and achieving low cost cellulose aerogel preparation.
The preparation of lightweight and porous green cellulose aerogel under normal pressure is realized, reducing production costs, avoiding environmental and safety hazards caused by solvent volatility, and simplifying the process flow.
Smart Images

Figure CN119161625A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing cellulose aerogel. Background Art
[0002] Aerogel is an ultra-light structure with a three-dimensional porous network. Due to its advantages such as high specific surface area, high porosity, low density, and low thermal conductivity, it has a wide range of applications in thermal insulation, air filtration, catalyst carriers, sound absorption and noise reduction, and water purification. Aerogels prepared using synthetic polymers or petroleum-based plastics are difficult to degrade, causing long-term ecological and environmental problems. With the introduction of the "dual carbon" strategy and the enhancement of people's environmental awareness, the development of green, renewable, and degradable green biomass aerogels has become a research hotspot in recent years.
[0003] Cellulose is a natural high-molecular polysaccharide composed of glucose. It is the most abundant renewable biomass resource in nature and is widely found in biomass materials such as wood, cotton, hemp, and straw. It has good biocompatibility and degradability, and is one of the ideal materials for preparing green renewable aerogels.
[0004] At present, various aerogels including cellulose aerogels are mainly prepared by removing the solvent from the wet gel. Since the huge surface tension between the solvent at the volatile interface and the internal network structure can easily cause the collapse of the aerogel structure during the solvent removal process, current research mostly uses supercritical drying or freeze drying to prepare aerogels. However, both methods require special equipment, harsh conditions (supercritical, high pressure, ultra-low temperature, high vacuum), complex processes, etc., which greatly increase the production cost of aerogels and limit the further production and application of aerogel materials. Therefore, there is an urgent need to explore a low-cost aerogel production process.
[0005] In recent years, some work has explored drying strategies for preparing aerogels under normal pressure conditions. We note that these strategies mainly use low surface tension organic solvents (ethanol, acetone, etc.) to replace the high surface tension solvents inside the wet gel, thereby achieving drying under normal pressure conditions. However, this strategy faces two problems. One is that a large amount of organic solvents are wasted during the replacement process, and the other is the potential environmental and safety risks brought about by the organic solvents during the volatilization process. Therefore, it is necessary to construct a normal pressure production process for aerogels that can be achieved without solvent replacement.
[0006] In summary, building a convenient and low-cost green biomass aerogel production technology is still an urgent problem to be solved. Summary of the invention
[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a method for preparing cellulose aerogel by drying at normal pressure, which method does not require expensive organic solvents for solvent replacement during the preparation process and can prepare green cellulose aerogel with light weight and porous characteristics.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows.
[0009] The present invention provides a method for preparing aerogel by drying at normal pressure, characterized in that the method comprises the following steps: (1) a mixed solution consisting of a nanocellulose dispersion, a surfactant, and a hardly soluble or insoluble carbonate powder; (2) the mixed solution is foamed by high-speed stirring to form a wet foam precursor; (3) the wet foam precursor is soaked in an acidic solution to obtain a solidified wet foam; and (4) the solidified wet foam is dried under normal pressure to obtain an aerogel material.
[0010] In some embodiments of the present invention, in the mixed solution, the nanocellulose is a cellulose nanofiber with surface carboxylation; optionally, the surfactant includes at least one selected from sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium hexadecyl sulfate, sodium hexadecylbenzene sulfonate, sodium hexadecyl sulfonate, sodium octadecyl sulfate, sodium octadecyl sulfonate, and sodium octadecylbenzene sulfonate; optionally, the poorly soluble or insoluble carbonate powder includes at least one selected from calcium carbonate, barium carbonate, zinc carbonate, magnesium carbonate, and manganese carbonate.
[0011] In some embodiments of the present invention, the mass ratio of the nanocellulose dispersion, the surfactant, and the insoluble carbonate powder in the mixed solution is (0.5-2wt%): (0.1-0.3wt%): (0.02-0.1wt%).
[0012] In some embodiments of the present invention, in step (2), the mixed solution is stirred by a mechanical stirrer, first by stirring at a speed of 500-1000 rpm for 30 minutes to mix evenly, and then the speed is increased to 2000-4000 rpm for high-speed stirring and foaming to form a wet foam precursor.
[0013] In some embodiments of the present invention, in step (3), the acidic solution is at least one of aqueous solutions including sulfuric acid, hydrochloric acid, nitric acid, acetic acid, acetic acid, and citric acid, and its concentration is 0.5-2wt%.
[0014] In some embodiments of the present invention, in step (3), the wet foam precursor is immersed in an acidic solution for 24-36 hours to obtain a solidified wet foam.
[0015] In some embodiments of the present invention, in step (4), the solidified wet foam is dried under normal pressure in a conventional normal pressure oven at 40-60° C. for 24-36 hours to obtain an aerogel material.
[0016] In some embodiments of the present invention, the solidified wet foam is dried under normal pressure, and during the drying period, a piece of ordinary paper is covered on the outside of the container where the wet foam is located.
[0017] Compared with the prior art, the advantages of the present invention are:
[0018] (1) The present invention provides a method for preparing biomass aerogel by drying at normal pressure, which avoids the supercritical drying and freeze-drying methods used in traditional aerogel preparation methods, and has the advantages of simple process, low production cost, and suitability for large-scale production.
[0019] (2) The method described in the present invention cleverly utilizes nanocellulose to build a strong three-dimensional network structure with the help of a foam template, which is sufficient to resist the structural collapse caused by the surface tension generated by water volatilization during the drying process under normal pressure conditions. This strategy avoids the replacement step of using low surface tension organic solvents, which not only saves production costs, but also avoids the environmental and safety hazards caused by solvent volatilization during the production process.
[0020] (3) The cellulose aerogel prepared by the atmospheric pressure drying method of the present invention uses cellulose as a matrix and is a green, environmentally friendly, renewable and degradable biomass raw material; the prepared aerogel exhibits the characteristics of being lightweight and porous. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 Schematic diagram of the preparation process.
[0023] Figure 2 The morphology of the cellulose aerogel after drying according to the methods described in Examples 1-5 of the present invention is shown, wherein a corresponds to Example 2, b corresponds to Example 3, c corresponds to Example 1, d corresponds to Example 4, and e corresponds to Example 5.
[0024] Figure 3 Two modes of the drying process are shown, wherein a corresponds to the drying in Example 8 in which the beaker is not covered with paper, and b corresponds to the drying in Examples 1-7 in which an A4 paper is covered on the beaker.
[0025] Figure 4 The external morphology and radial cross-section photos of the aerogel after drying by two drying methods are shown, where a and c are for Example 8, and b and d correspond to Example 1.
[0026] Figure 5 The external morphology and radial cross-section photos of the aerogel after drying at three different drying temperatures are shown, where a and d correspond to Example 7, b and e correspond to Example 6, and c and f correspond to Example 1.
[0027] Figure 6 This is a photograph showing the aerogel prepared according to Example 1 of the present invention on a dandelion.
[0028] Figure 7 The figure is a scanning electron microscope image of a cube cut of aerogel prepared according to Example 1 of the present invention and the corresponding sample. DETAILED DESCRIPTION
[0029] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0030] The raw materials used in the embodiment:
[0031] Cellulose nanofibers (CNF) were prepared by combining 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) oxidation with mechanical treatment; the difference in the degree of carboxylation on the CNF surface was achieved by regulating the amount of sodium hypochlorite (NaClO) added during the reaction. The specific preparation process of CNF is as follows: take 1g of cellulose and disperse it evenly in 100mL of deionized water. Add 0.016g of TEMPO and 0.1g of NaBr, then add NaClO solution, and add sodium hydroxide dropwise during the reaction to keep the pH of the reaction system at about 10. After the reaction, the cellulose was washed, sonicated and concentrated to obtain CNF with a concentration of 2wt%. The obtained CNF is named CNF-x, where x represents the number of millimoles of sodium hypochlorite added per gram of absolutely dry cellulose, specifically: CNF-2.5, CNF-5, CNF-7.5, CNF-10, CNF-12.5.
[0032] Example 1
[0033] This embodiment provides a method for preparing aerogel by drying at normal pressure, the method comprising the following steps:
[0034] (1) A mixed solution of 50 g CNF-7.5 (concentration: 2 wt%) cellulose nanofibers, 0.1 g CaCO3 powder, 0.05 g SDS and 50 g deionized water was prepared. The mixed solution was stirred at 1000 rpm for 30 min by a mechanical stirrer, and foaming was avoided during the process to ensure full mixing.
[0035] (2) The rotation speed was increased to 2000 rpm and stirred for 5 min, and the mixed solution in step (1) was foamed by high-speed stirring to form a wet foam precursor. At this time, CNF and CaCO3 powder were dispersed between the foam walls to form a temporary structure without forming a stable connection.
[0036] (3) Pour the wet foam prepared in step (2) into a 1wt% dilute hydrochloric acid solution and soak for 24 hours to obtain solidified wet foam. In this step, the acid infiltrates from bottom to top along the foam cell wall and reacts with the CaCO3 between the foam cell walls to generate CaCO3. 2+ ; Subsequently, the in situ generated Ca 2+ It forms ionic complexes with the carboxylate groups on the surface of CNF to build a stable and strong foam network structure.
[0037] (4) The solidified wet foam was then taken out and placed in a beaker, a piece of A4 paper was covered on the beaker, and the beaker was placed in an oven and dried at 50 °C for 24 h to obtain a cellulose aerogel material, which was named 7.5CA.
[0038] Example 2
[0039] This embodiment provides a method for preparing aerogel by drying at normal pressure, except that the cellulose nanofibers described in step (1) are replaced by CNF-7.5 with CNF-2.5, and other conditions are exactly the same as those in Example 1, and the aerogel is named 2.5CA.
[0040] Example 3
[0041] This embodiment provides a method for preparing aerogel by drying at normal pressure, except that the cellulose nanofibers described in step (1) are replaced by CNF-5 instead of CNF-7.5, and other conditions are exactly the same as those in Example 1, and the aerogel is named 5CA.
[0042] Example 4
[0043] This embodiment provides a method for preparing aerogel by drying at normal pressure, except that the cellulose nanofibers described in step (1) are replaced by CNF-10 instead of CNF-7.5, and other conditions are exactly the same as those in Example 1, and the aerogel is named 10CA.
[0044] Example 5
[0045] This embodiment provides a method for preparing aerogel by drying at normal pressure, except that the cellulose nanofibers described in step (1) are replaced by CNF-7.5 with CNF-12.5, and other conditions are exactly the same as those in Example 1, and the aerogel is named 12.5CA.
[0046] Example 6
[0047] This embodiment provides a method for preparing aerogel by drying at normal pressure. Except that the "drying at 50°C for 24 hours" in step (4) is replaced by "drying at 70°C for 24 hours", the other conditions are exactly the same as those in Example 1.
[0048] Example 7
[0049] This embodiment provides a method for preparing aerogel by drying at normal pressure. Except that the "drying at 50°C for 24 hours" in step (4) is replaced by "drying at 90°C for 24 hours", the other conditions are exactly the same as those in Example 1.
[0050] Example 8
[0051] This embodiment provides a method for preparing aerogel by drying at normal pressure. Except that the "a piece of A4 paper is covered on the beaker" in step (4) is replaced by "the beaker is not covered with A4 paper", the other conditions are exactly the same as those in Example 1.
[0052] The density and porosity of the aerogels prepared in the above examples are listed in Table 1.
[0053] Table 1 <![CDATA[Density (kg / m 3 )]]> Porosity (%) Example 1 11.56 99.28 Example 4 11.89 99.26 Example 5 9.20 99.43
[0054] Example 9
[0055] This embodiment further provides a method for preparing a composite aerogel. By further modifying the surface of the aerogel with tannin, an aerogel with photothermal conversion properties can be prepared for use in solar-driven seawater desalination applications. The specific preparation method is as follows:
[0056] The aerogel prepared in Example 1 was immersed in a 0.3 wt % tannin aqueous solution for 12 h, and then transferred to a 0.2 wt % ferric chloride aqueous solution and immersed for 12 h. The sample was taken out and placed in an oven to dry, thereby obtaining a photothermal aerogel named 7.5TCA.
[0057] The 7.5TCA aerogel sample was placed under a simulated xenon lamp light source of 1 standard sun intensity for a solar-driven desalination performance test. During the test, the weight change of the sample was monitored by a microbalance, and the desalination rate of the sample could be calculated based on the weight change.
[0058] The evaporation rate of 7.5TCA measured under 1 standard sun intensity is 3.58 kg m -2 h -1 , the energy utilization efficiency is 97.19%, which is much higher than the theoretical evaporation rate limit of pure water (1.6 kg m -2 h -1 This is mainly due to the aerogel's excellent photothermal conversion ability, rapid water transport and excellent energy limitation ability. This also further demonstrates the application potential of the aerogel in the field of efficient seawater desalination.
[0059] It should be noted that, in this application, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0060] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing aerogel by drying at normal pressure, characterized in that: The method comprises the following steps: (1) a mixed solution consisting of a nanocellulose dispersion, a surfactant, and a poorly soluble or insoluble carbonate powder; (2) the mixed solution is foamed by high-speed stirring to form a wet foam precursor; (3) soaking the wet foam precursor in an acidic solution to obtain a solidified wet foam; (4) Drying the solidified wet foam under normal pressure to obtain an aerogel material.
2. The method according to claim 1, characterized in that In the mixed solution, the nanocellulose is a cellulose nanofiber with surface carboxylation; Optionally, the surfactant includes at least one selected from sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium hexadecyl sulfate, sodium hexadecylbenzene sulfonate, sodium hexadecyl sulfonate, sodium octadecyl sulfate, sodium octadecyl sulfonate, sodium octadecylbenzene sulfonate; Optionally, the poorly soluble or insoluble carbonate powder includes at least one selected from calcium carbonate, barium carbonate, zinc carbonate, magnesium carbonate, and manganese carbonate.
3. The method according to claim 1, characterized in that The mass ratio of the nanocellulose dispersion, the surfactant and the insoluble carbonate powder in the mixed solution is (0.5-2wt%): (0.1-0.3wt%): (0.02-0.1wt%).
4. The method according to claim 1, characterized in that: In step (2), the mixed solution is stirred by a mechanical stirrer, first by stirring at a speed of 500-1000 rpm for 30 minutes to mix evenly, and then the speed is increased to 2000-4000 rpm for high-speed stirring and foaming to form a wet foam precursor.
5. The method according to claim 1, characterized in that In step (3), the acidic solution is at least one of aqueous solutions including sulfuric acid, hydrochloric acid, nitric acid, acetic acid, acetic acid, and citric acid, and its concentration is 0.5-2wt%.
6. The method according to claim 1, characterized in that In step (3), the wet foam precursor is immersed in an acidic solution for 24-36 hours to obtain a solidified wet foam.
7. The method according to claim 1, characterized in that In step (4), the solidified wet foam is dried under normal pressure in a common normal pressure oven at 40-60° C. for 24-36 hours to obtain an aerogel material.
8. The method according to claim 7, characterized in that The solidified wet foam is dried under normal pressure, and during the drying period, a piece of ordinary paper is covered on the outside of the container where the wet foam is located.
9. An aerogel material prepared under normal pressure conditions, characterized in that: The invention is prepared by the method according to any one of claims 1 to 8.
